The Influence of Using Genially Website Learning Media in Indonesian Language Subject of the Learning Outcomes of 8th Grade Students at SMP Negeri 3 Panca Rijang - Nur Sahira Saleh; Madaling Madaling; Hasanuddin Hasanuddin (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effect of using the Genially website interactive media on the Indonesian language learning outcomes of 8th-grade students at SMP Negeri 3 Panca Rijang. This research uses a quantitative method. The research sample consists of 44 students from the 8th grade at SMP Negeri 3 Panca Rijang. The data collection techniques used are documentation to obtain the school profile, learning situation conditions, school facilities, the number of 8th-grade students at SMP Negeri 3 Panca Rijang, and a multiple-choice test. The results of this study indicate that there is an influence of using the Genially website interactive media on the Indonesian language learning outcomes of 8th-grade students at SMP Negeri 3 Panca Rijang. This is evidenced by the students' learning outcomes. Based on the analysis of the research results, the average score is found to be Mx = 85.90 > My = 57.72, which leads to the conclusion that this study shows a significant impact of using the Genially interactive website media on students' learning outcomes.